2019
DOI: 10.1088/2051-672x/ab411b
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of FeCrNiMoCBSi amorphous / nanocrystalline composite coatings via plasma spraying process

Abstract: Fe-based amorphous coating technology is recognized as an attractive surface modification method owing to superior physical and chemical properties. Novel FeCrNiMoCBSi coatings were prepared on marine F22 steels by plasma spraying with various spraying powers. Morphologies and microstructures were characterized by scanning electron microscope (SEM), x-ray diffraction (XRD), transmission electron microscope (TEM) and differential scanning calorimetry (DSC). Results showed that the as-sprayed coatings were mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The corrosion behaviour for Fe-based MG composite coatings in different environments was primarily influenced by composition, amorphicity level and defective regions (porosity, inter-splat) [66,124,128,137,141,231,374]. In recent years, the corrosion properties of in-situ Febased MG composite coatings have been widely investigated [121,133,138,142,161,169,265,277,298,[375][376][377][378][379][380][381][382][383][384][385][386][387]. For instance, Lin et al [121] observed that porosities, inter-splats and oxides had deleterious effect on the corrosion behaviour of arc-sprayed FeNiCrB-SiNbW MG composite coating.…”
Section: In-situ Composite Coatingsmentioning
confidence: 99%
“…The corrosion behaviour for Fe-based MG composite coatings in different environments was primarily influenced by composition, amorphicity level and defective regions (porosity, inter-splat) [66,124,128,137,141,231,374]. In recent years, the corrosion properties of in-situ Febased MG composite coatings have been widely investigated [121,133,138,142,161,169,265,277,298,[375][376][377][378][379][380][381][382][383][384][385][386][387]. For instance, Lin et al [121] observed that porosities, inter-splats and oxides had deleterious effect on the corrosion behaviour of arc-sprayed FeNiCrB-SiNbW MG composite coating.…”
Section: In-situ Composite Coatingsmentioning
confidence: 99%
“…Taking advantage of this feature, the preparation of coatings containing nanocrystals can greatly improve the wear resistance of the coatings. 71 Sun et al 72 prepared an Fe-based amorphous coating with a wear resistance 170 times that of the LA141 magnesium alloy substrate. Ma et al 73 prepared Fe-based amorphous coatings by HVOF.…”
Section: Wear Resistancementioning
confidence: 99%
“…The plasma spray coating makes the microstructure harder with smaller grains. The composite coatings facilitated the fabrication of tribo-film with an optimum microstructure [9][10][11]. The adhesion strength of the plasma spray coatings determines the long-term durability, which further increases the charge transfer resistance of the coatings in a saline environment.…”
Section: Introductionmentioning
confidence: 99%